Esthetic and theory of the obscene in modern negro-africaine literature : the study cases of « places of the parties » and « hermina » by sami tchak - (:unkn) unknown (My University, 2014)
If we accept the idea that unlike modern novel, contemporary novel does not absolutely seek to recreate the human figure, but rather thinks of it as a « trans-individual » image of the human being, then the taking into account of the Obscene in the « Negro-African » literature's context of these last 30 years makes sense. The ludicrous break with the linearity and the use of language as cathartic effect enable to express differently a future which is more and more beyond our control.We are trying to understand the upsurge of the Obscene in the new african fiction writings as a contemporary symptom and a new approach on the part of tthe authors of the fourth generation, to truly comandeer the sense of the word « individual » in the « Negro-African » context.If, according to the Petit Larousse dictionary, the Obscene is « what offends openly the modesty through sexual representations », it has deep ethical consequences in a « Negro-African » context where strong cultural taboos on sexual initmacy productions exist. We will try to explain at what cost the Obscene can set itself up as an element of literarity or as a theory able to sustain the subject practising it. However, is a community still possible beyond the disruption of the ethical values caused by a possible aesthetic of the Obscene ?
Keywords: African Research